The Role of Social Media in Promoting Halal Fashion Among The Youth Generation - Syifa Rahmania, Dwiana; Prima Dwi Priyatno (Jurnal At-Tamwil: Kajian Ekonomi Syariah, 2025)
Purpose – This study aims to explore the role of social media in promoting halal fashion among the youth generation, particularly focusing on the influence of digital platforms on purchasing behavior and perceptions of modest fashion. The research seeks to understand how fashion brands utilize social media to target young Muslim consumers and the effectiveness of these strategies in promoting halal lifestyles. Design/Methods/Approach – A qualitative approach was employed, utilizing a comprehensive literature review to analyze existing studies and theories on halal fashion, social media marketing, and consumer behavior. Various academic journals, books, and credible online sources were examined to gather relevant data. Findings – The study finds that social media platforms, such as Instagram, TikTok, and YouTube, significantly influence Muslim youth’s fashion choices. Social media not only serves as a marketing tool but also facilitates community engagement and education around halal fashion. Influencer marketing plays a crucial role in shaping purchasing intentions, while challenges regarding authenticity and consumer trust are evident. Research Implications/Limitations – The study's limitations include its reliance on secondary data and the evolving nature of social media trends, which may affect the long-term applicability of the findings. Additionally, the research focuses primarily on Indonesian youth, which may limit its generalizability to other regions. Originality/Value – This study contributes to understanding how social media influences halal fashion consumption, shedding light on the intersection of religious values, modern trends, and digital marketing strategies. It offers insights for halal fashion brands on effectively engaging young Muslim consumers. Future research could explore the role of emerging platforms and consumer behavior changes in the halal fashion market.